Immune Lymphocyte Infiltrate and its Prognostic Value in Triple-Negative Breast Cancer - Huertas-Caro, Carlos Alexander; Ramirez, Mayra Alejandra; Gonzalez-Torres, Henry J.; Sanabria-Salas, María Carolina; Serrano-Gómez, Silvia J. (Frontiers in Oncology, 2022)
Triple-negative breast cancer (TNBC) occurs more frequently in young (<50 years) non-Hispanic black and Hispanic/Latina women. It is considered the most aggressive subtype of breast cancer, although, recently, immune infiltrate has been associated with long-term survival, lower risk of death and recurrence, and response to neoadjuvant chemotherapy. The aim of this review was to evaluate the clinical impact of the immune infiltrate in TNBC by discussing whether its prognostic value varies across different populations. A comprehensive systematic search in databases such as PubMed and Web of Science was conducted to include papers focused on tumor-infiltrating lymphocytes (TILs) in TNBC in different population groups and that were published before January 2021. TNBC patients with higher levels of TILs had longer overall survival and disease-free survival times compared with TNBC patients with low TIL levels. Similar results were observed for CD4+, CD8+ TIL populations. On the other hand, patients with high TIL levels showed a higher rate of pathological complete response regardless of the population group (Asian, European, and American). These results altogether suggest that TIL subpopulations might have a prognostic role in TNBC, but the underlying mechanism needs to be elucidated. Although the prognosis value of TILs was not found different between the population groups analyzed in the revised literature, further studies including underrepresented populations with different genetic ancestries are still necessary to conclude in this regard.